(untitled) (The Review of Diabetic Studies, 2025)
Prehospital hemorrhage remains a leading cause of preventable death, prompting widespread adoption of clotting and hemostatic adjuncts in EMS systems. This systematic review evaluates the effectiveness of clotting-assisted hemorrhage control in the prehospital environment, focusing on hemostatic performance and early clinical endpoints. Evidence from civilian and military-translated cohorts indicates that modern hemostatic dressings containing kaolin or chitosan achieve bleeding control rapidly in compressible wounds, improving shock indices at emergency department handover. Adjunctive granular and foam agents provide additional options for junctional and irregular anatomical sites when conventional gauze and pressure are insufficient. Reported outcomes suggest higher rates of initial hemostasis, potential reductions in early mortality proxies (survival to hospital), and acceptable safety profiles when EMS providers receive structured simulation-based training. However, heterogeneity in indications, injury severity, and outcome definitions persists, limiting pooled effect estimates. The review underscores that clotting aids can enhance field hemostatic performance when embedded within standardized hemorrhage control protocols and continuous competency programs.